Empowerment or Endangerment? The Nutritional Consequences of Female Employment in Rural India - Bandana Mondal; Prasenjit Sarkhel (ZBW – Leibniz Information Centre for Economics, 2024)
This paper investigates the relationship between female employment and nutritional status in rural India, using data from the National Family Health Survey-5 (NFHS-5). Constructing a nutrition index that captures the extent of food intake, we find that employed women are nutritionally worse off than their unemployed counterparts. This negative effect persists even after correcting for the potential endogeneity of female employment and nutrition, with robustness checks across different food items, alternative measures such as Body Mass Index (BMI), and district-level economic conditions, proxied by nightlights data. We also find suggestive evidence of greater intra-household food disparity between employed women and their male counterparts. Further analysis reveals that spousal violence—exacerbated by female employment—plays a significant role in undermining women's nutritional outcomes, while the positive effect of increased decision-making power is comparatively weaker. This dynamic is evident across all wealth quintiles, suggesting that higher economic status does not mitigate these adverse effects. The findings highlight the need for employment policies that incorporate nutritional support for working women, as well as interventions to reduce intra-household conflict, ensuring that employment translates into both economic and health gains for women in rural India.
Keywords: D13; I14; 330; Nutritional status; Female Employment; NFHS-5; Instrumental Variable